Systemic Immune-Inflammation Index as a Potential Indicator of COVID-19 Severity in a Tertiary Hospital in Indonesia - Hamdan, Angkasa Ramatuan; Fianza, Pandji Irani; Hartantri, Yovita (Althea Medical Journal, 2025)
Background: The progression of coronavirus disease 2019 (COVID-19) to severe stages is strongly influenced by host immunity and inflammatory. The Systemic Immune-Inflammation Index (SII) is a novel biomarker reflecting both immunity and inflammation. This study aimed to analyze differences in SII according to COVID-19 severity.Methods: A cross-sectional study was conducted using medical records of COVID-19 patients hospitalized at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, between March 2020 and August 2021. SII was calculated as the absolute neutrophil count and platelet count divided by the absolute lymphocyte count obtained from peripheral blood samples. COVID-19 severity was classified based on oxygen saturation (SpO₂). Receiver operating characteristic (ROC) curve and the area under the curve (AUC) were used to evaluate the discriminatory ability of SII. Results: Of the 1,192 patients included, 410 (34.3%) had severe symptoms and 782 (65.7%) had mild to moderate symptoms. The median SII at admission was significantly higher in severe symptoms [1779 x 109 /L (IQR 46-40416)] compared with mild to moderate symptoms [880 x 109 /L (IQR 14.5-23280)]; p<0.001. ROC analysis showed an SII cut-off of 1244 with an AUC of 0.695 (95% CI 0.668–0.721), sensitivity 65.9%, and specificity 66.2%.Conclusions: SII may serve as a potential biomarker for predicting COVID 19 severity. Its simplicity and availability from routine blood counts make it particularly valuable for early risk stratification, especially in resource-limited settings. Moreover, early recognition of elevated SII could support timely interventions, prevent disease progression, and improve clinical outcomes.